Enhancing sustainable forest management in Cameroon through a model forest based approach - Jum, C.N.; Diaw, C.; Nguiebouri, J.; Zoa, M. (2007)
A range of countries have sought more equitable governance of their natural resources, by devolving decision-making and resource control to local populations. In 1994, Cameroon adopted a new law granting local communities the possibility of greater control over forests, principally in response to donor conditionality on Structural Adjustment Loans (SALs). However, the enactment of the law lacked signifi cant domestic support. Confl icting interests and Cameroon’s highly centralized administrative machinery have prevented effective devolution of forest management. In 2003, the Center for International Forestry Research (CIFOR) and a consortium of institutional stakeholders started the Model Forest Project in Cameroon. This project is part of the International Model Forest Network (IMFN). The goal of the IMFN is to assist in the development of sustainable management of forests around the world, while taking into account the needs of local communities. In 2005, the government of Cameroon recognized Campo Ma’an and Dja et Mpomo as model forest sites. The partnership involved, policy dimensions, government commitment, accomplishment to date and its contributions to national and sub regional forestry programmes are discussed.